An Act to Amend Militia Law, Chapter 16 [H. B. No. 515] in General Laws of the State of Texas Passed at the Regular Session of the Twenty-First Legislature (1889). Article 3294 - (:unkn) unknown (My University, 1889)
And it shall not be lawful for any body of men whatsoever, other than the regularly organized volunteer guard, to associate themselves together as a military company or organization, or to parade in public with arms in any part of the state, without the license of the governor therefor.
Keywords: MILITIAS